Component-Based Software Engineering 13th International Symposium, CBSE 2010, Prague, Czech Republic, June 23-25, 2010. Proceedings - Grunske, Lars.; Reussner, Ralf.; Plasil, Frantisek; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 13th International Symposium on Component-Based Software Engineering, CBSE 2010, held in Prague, Czech Republic, in June 2010. The 14 revised full papers presented were carefully reviewed and selected from 48 submissions. The papers are organized in topical sections on component-based embedded systems; component-based adaptive systems; component interfaces, contracts and adapters of component-based systems; and composition and /de)-composition of component-based systems.
Component-Based Embedded Systems -- Reliability Analysis of Component-Based Systems with Multiple Failure Modes -- Comparison of Component Frameworks for Real-Time Embedded Systems -- A Three-Tier Approach for Composition of Real-Time Embedded Software Stacks -- Bridging the Semantic Gap between Abstract Models of Embedded Systems -- Component-Based Adaptive Systems -- Reliable Dynamic Reconfigurations in a Reflective Component Model -- Reactive Model-Based Control of Reconfiguration in the Fractal Component-Based Model -- Enabling on Demand Deployment of Middleware Services in Componentized Middleware -- A Self-healing Component Sandbox for Untrustworthy Third Party Code Execution -- Component Interfaces, Contracts and Adapters of Component-Based Systems -- Component Contracts in Eclipse - A Case Study -- Automated Creation and Assessment of Component Adapters with Test Cases -- An Empirical Study of the Component Dependency Resolution Search Space -- Composition and (De)-composition of Component-Based Systems -- Component Composition Using Feature Models -- Restructuring Object-Oriented Applications into Component-Oriented Applications by Using Consistency with Execution Traces -- (Behavioural) Design Patterns as Composition Operators.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Programming Techniques; Artificial Intelligence (incl. Robotics).